2013
DOI: 10.1586/erm.12.116
|View full text |Cite
|
Sign up to set email alerts
|

Why do participants enroll in population biobank studies? A systematic literature review

Abstract: Therapeutic misconception has been extensively studied and addressed within clinical trials. An equivalent in the genetic research context has been identified as diagnostic misconception. There is not much data on this phenomenon in population-based biobank studies. Since misconceptions may generate undue motives to enroll, the authors aimed at reviewing studies addressing the reasons to participate in biobank studies. The main databases were searched using relevant keywords. Studies were included if peer-revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 64 publications
(120 reference statements)
4
74
1
Order By: Relevance
“…The majority of people in this study were enthusiastic about participating in genomics research, and the reasons people gave for being willing to participate in genomics research fell into four main overarching themes: to help others outside the family (altruism); to help family members; for personal health benefit; and for personal curiosity and improved understanding. The altruistic motivation has been previously reported (e.g., Lemke et al 2010), as has the expectation of personal benefit (Nobile et al 2013). To some extent, our findings provide some evidence of the "therapeutic misconception" (Nobile et al 2013) in that some of the reasons people provided for participating in genomics reason suggested that they assumed that they would receive specific personal results through their participation, e.g., "To see if I'm at high risk for any of those diseases".…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The majority of people in this study were enthusiastic about participating in genomics research, and the reasons people gave for being willing to participate in genomics research fell into four main overarching themes: to help others outside the family (altruism); to help family members; for personal health benefit; and for personal curiosity and improved understanding. The altruistic motivation has been previously reported (e.g., Lemke et al 2010), as has the expectation of personal benefit (Nobile et al 2013). To some extent, our findings provide some evidence of the "therapeutic misconception" (Nobile et al 2013) in that some of the reasons people provided for participating in genomics reason suggested that they assumed that they would receive specific personal results through their participation, e.g., "To see if I'm at high risk for any of those diseases".…”
Section: Discussionmentioning
confidence: 82%
“…The altruistic motivation has been previously reported (e.g., Lemke et al 2010), as has the expectation of personal benefit (Nobile et al 2013). To some extent, our findings provide some evidence of the "therapeutic misconception" (Nobile et al 2013) in that some of the reasons people provided for participating in genomics reason suggested that they assumed that they would receive specific personal results through their participation, e.g., "To see if I'm at high risk for any of those diseases". However, our findings also suggest that people anticipated that they could personally benefit in a different way: by gaining knowledge more generally.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This meant that field staff had to develop verbal constructs to explain, for example, what genes are and how they are inherited, and to be able to distinguish between diseases that are monogenic or are polygenic and multifactorial in nature. An important concern was that the study might introduce therapeutic and diagnostic expectations [75,76]. Participants were informed that if there were clear clinical indications of disease, then they would be referred to a local medical practitioner or health facility for treatment according to local standards of care.…”
Section: Discussionmentioning
confidence: 99%